Regulatory sRNAs in Cyanobacteria - Hu, Jinlu; Wang, Qiang (Frontiers in Microbiology, 2018)
As the transcriptional and post-transcriptional regulators of gene expression, sRNAs (small RNAs) play important roles in every domain of life in organisms. It has been discovered gradually that bacteria possess multiple means of gene regulation using RNAs. Has been continuous to be model organisms for photosynthesis, metabolism, biotechnology, evolution and nitrogen fixation for many decades, cyanobacteria, one of the most ancient life forms, constitute all kinds of photoautotrophic bacteria and exist in almost any environment on this planet. It is believed that a complex RNA-based regulatory mechanism have functioned in cyanobacteria to adapt changes and stresses in diverse environment. Although lagging far behind other model microorganisms such as yeast and E. coli, more and more non-coding regulatory sRNAs have come into view in cyanobacteria during the past decades. In this article, by focusing on cyanobacterial sRNAs, the approaches for sRNAs detecting and targeting will be summarized, four major mechanisms and regulatory functions will be generalized, eight types of cis-encoded sRNA and four types of trans-encoded sRNAs will be reviewed in detail, and their possible physiological functions will be further discussed.